VARIABILITY OF INDIAN SUMMER MONSOON : RELATIONSHIP WITH GLOBAL SST ANOMALIES - VERMA , R. K. (MAUSAM, 1994)
(iloh,tlcurr("!,1111111 ll111p .o; uflhe SlIllll1lt" r mUn!\4 lOn prt>cipil:lliull anomalies a nti St"a SU l f.IC(" Tt"mpt" 1 a1lln"' (SST) a nUllul!it'.'i are pTt'St'IlI("d . n lir1 ) -)l' /u (1950..1479) rime St' 1; ("S uf 11l0n...nnn ind("x b co rn' l a h~d ....; Ih Iht" SST tillll' Sl'riCS al t"nch 1° ;<2° latitLIl1co! u nl:iluJt" box uf th t" \\(1(111 (>I,:eans usi ng COADS (Comprehensive O..:ean Allno...pl1("fl." Dala S('1)dn ta ttl "3riOUS timc IJgs o f lUonth s (i.t' .. l1luI11 h,'S of year s p recedi ng 'lI1.1 conc urrcnI lu Ihe 1ll011Stllll1-)l'at) , Ctl lTclal ion..mups :'I ll' pn.-pUTl,.f 111111 Illaly"I'" 1(1 i.lclltify Il' IN."Oll lle ct it ln "-' Ilf llln ll....oon pTt'I,:ipil<ttiun wilh glubal S ~Ts. It is I'olin.! th ai tlll' lag,orrelatiuns .... ilh SST (Will 1:('01(31 and t'ilstt"m t'lluHt orial Padlic (Ninu-rl'l!innilire suggl·..liw of IWlI I>p t' S o f inlt"raetjuns .....ith Ihe munsoun. The first on e, .... h il.:h sho ws pmili\'c <:orre lnlio n of summer monsoon pf('\.-ipililtion anoll1alit"s ",i lh Ihe ct"nlral and l":Jsl ..-mequaturial P<lciftc SST nnoUlal ies aboul a yea r be fore lilt" 1l10 nsollfl. sUggl°.!>1Sthat lhe monsoon which follo ws abmlt a )'t'lir la ll'r ur tX'currence ofwaml t"pisode of EI..Nin~ Suut hem Oscillatiun (ENSO) is generally ....-eltc It is also suggestetJ Ihal this inleract io n might be taki ng place lhruugh Ihe in llue nce or nOr1h em hemisp here int er tempera tures. Th e seco nd I)-PC of inleraclion of equ alorial Paci fic SST ....i lh mon soon is revealed through the strung n~al ive co rrela tio ns bqinning befo re lh e summer monsoo n an d continuing ....; lh g~ a l er magnitud e an d o~ r ....i der extent. suuest ing th ai a .....arm SST anomaly j ust precedine anll concurrent to monsoon ~aso n weaken s th e monsson. AiNt"li intcf<n'lions bctween Ihe Indian Ocean and monsoon are also emph a si ~d in the anal ysis. Two key ~ginns are ide nt ified. Th e cen tra l Indian Ocun south o f th e equalor shoW!strong positive corre la tions during (he lalt' no n hl'm ",inler a nd spring. Th e other key Tq!'ion is in the north Ind ian Geran. Th e correlations are significanlly nt'ga li\'e. Some teleconnections with th e Atlantic basin are also revealed which are ralhe rdifficuh to explain but ma y find usefu l ap plications in monitoring and long-range forecas line of the monsoon.